1992
DOI: 10.1159/000168436
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Immunogenicity and Efficacy of Hepatitis B Vaccine in Hemodialysis Patients

Abstract: Although the efficacy of hepatitis B vaccines in patients under chronic hemodialysis treatment has been well documented, the persistence of immunity in this population remains largely unknown. In this study we have followed 60 hemodiaysis patients up to 3 years after primary hepatitis B vaccination (four doses of recombinant hepatitis B vaccine; Engerix B, 20 mg/dose) to evaluate the persistence of immunity (as indicated by serum levels of antibody to hepatitis B surface antigen – anti-HBs – higher than or equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
92
3
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 9 publications
5
92
3
4
Order By: Relevance
“…Several studies [106,113,114,123,132,151] evaluated the long-term efficacy of the vaccine in HD patients and reported a decline of anti-HBs titers within 6 months to 4 years after vaccination. In a recent series [152], 36% (21/ 58) of HD patients showed loss of detectable anti-HBs titers over a 34-month follow-up; older age and longer duration of HD treatment were correlated with the decline of anti-HBs titers over time.…”
Section: Hbv Vaccination In Dialysis: Long-term Studiesmentioning
confidence: 99%
“…Several studies [106,113,114,123,132,151] evaluated the long-term efficacy of the vaccine in HD patients and reported a decline of anti-HBs titers within 6 months to 4 years after vaccination. In a recent series [152], 36% (21/ 58) of HD patients showed loss of detectable anti-HBs titers over a 34-month follow-up; older age and longer duration of HD treatment were correlated with the decline of anti-HBs titers over time.…”
Section: Hbv Vaccination In Dialysis: Long-term Studiesmentioning
confidence: 99%
“…However, it has been repeatedly observed that chronic uremic patients with or without dialysis treatment have an impaired immune response to the HBV vaccine. 63,64 The seroconversion rate is only 50-73% 65 in contrast to more than 90% in healthy subjects. Some scholars believe that dialysis patients with hypo-responsiveness to the HBV vaccine may be associated with cellular immune dysfunction.…”
Section: Discussionmentioning
confidence: 98%
“…Bu hastalarda T-lenfosit ve antijen sunan hücrelerde fonksiyon bozukluğu olduğu düşünülmektedir [13][14][15]. Bazı çalışmalarda diyalizsiz takip edilen KBH hastalarında daha yüksek antikor cevabının elde edilmesi, böbrek yetmezliğinin şiddeti ile immün cevabın korele olduğunu düşündürmektedir [13,16,17]. KBH hastalarında hepatit B aşılamasına yeterli cevap alınabilmesi için yüksek doz ve daha sık enjeksiyon yapılması önerilmiştir [10,18].…”
Section: Discussionunclassified